Respuesta :
c/7 = 6 1/7 ⇒ c = 43 ⇒ 43/7 = 6 1/7
Convert mixed fraction into a simple fraction
6 1/7 ⇒ (6 * 7 + 1)/7 = 43/7
c/7 = 43/7
proportionality:
a/b = c/d where ad = bc
a = c
b = 7
c = 43
d = 7
ad = bc ⇒ c7 = 7*43 ⇒ c7 = 301 ⇒ 7c/7 = 301/7 ⇒ c = 43
Convert mixed fraction into a simple fraction
6 1/7 ⇒ (6 * 7 + 1)/7 = 43/7
c/7 = 43/7
proportionality:
a/b = c/d where ad = bc
a = c
b = 7
c = 43
d = 7
ad = bc ⇒ c7 = 7*43 ⇒ c7 = 301 ⇒ 7c/7 = 301/7 ⇒ c = 43
c/7= 6 1/7
⇒ c/7= 6+ 1/7
⇒ c/7= 42/7+ 1/7
⇒ c/7= 43/7
⇒ c= 43
Final answer: c=43~
⇒ c/7= 6+ 1/7
⇒ c/7= 42/7+ 1/7
⇒ c/7= 43/7
⇒ c= 43
Final answer: c=43~